Epidemiology of Ureaplasma urealyticum and Mycoplasma hominis in the semen of male outpatients with reproductive disorders - Zhu, Xiaofei (Exp Ther Med, 2016)
The aim of the present study was to investigate the association between Mycoplasma infection and infertility in male outpatients among a Chinese population. Epidemiological data, including prevalence, age distribution and antibiotic resistance profile of patients with an Ureaplasma urealyticum or Mycoplasma hominis infection were collected between 2009 and 2012. Among the 7,374 individuals analyzed, 3,225 patients (43.7%) were determined to be positive for infection with U. urealyticum, M. hominis or for both Mycoplasmas. Among the positive cultures, U. urealyticum was detected most frequently, while M. hominis was rarely found. The age range of 25–34 years was the preferred period for the positive detection. Tetracyclines and josamycin were the most effective agents against both genital Mycoplasmas, including in the case of co-infection. Macrolides (erythromycin, roxithromycin, azithromycin, clarithromycin except for josamycin) were effective against the majority of U. urealyticum clinical isolates, but were naturally resisted by M. hominis in this study. Fluoroquinolones had the lowest activity against U. urealyticum, particularly in cases of M. hominis co-infection. Furthermore, fluoroquinolones showed a similar pattern of drug resistance against M. hominis to that of U. urealyticum. Antibiotic resistance did not vary significantly over the test period. Notably, an elevated multi-drug resistance rate was observed in patients co-infected with both Mycoplasmas. In light of the epidemiological characteristics of genital Mycoplasmas in male infertility patients, the present results may aid Chinese clinicians to implement rational drug usage and avoid the overuse of antibiotics.